Five-Phase Induction Motor DTC-SVM Scheme with PI Controller and ANN Controller. (2016) - Barik, Subodh Kanta; Jaladi, Kiran Kumar
Abstract: This paper analyze design of space vector modulation based direct torque controlled (DTC-SVM) five-phase induction motor incorporated with ANN controller and has given a comparison with PI controller. This ANN controller is employed to improve the control performance parameters such as reducing torque & flux ripple, reducing the settling and rise time compare to that of PI controller. The modelling and simulation is performed in MATLAB, it shows that with intelligent controlled the performance parameters have been improved and drive system could be operated at low speed. The proposed model is less complex, require a single ANN controller for decoupled flux and torque controlled.